Meningkatkan Nilai Produk Paguyuban Penghasil Gula Jawa Dusun Kliwonan Untuk Memasuki Pasar Nasional - Yohanes Satyayoga Raniasta (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
All members of the Kelapa-Mas community work as palm-sugar-maker in Kliwonan, Banjarharjo, Kalibawang District, Kulon Progo, Yogyakarta. The community has been producing palm sugar for generations and selling it to traditional markets around the village. There is a possibility that the community product could be developed to get a wider market and would give a better economic impact on the community. Through the UKDW Service Learning program in 2019, the community has been assisted to increase the value of their palm-sugar product. This assistance is carried out in 4 stages, First: counseling of good and hygienic production processes according to P-IRT standards, Second: assistance to product branding and packaging, Third: counseling and initiation of product marketing through online/digital and offline media, in collaboration with retail stores, and Fourth: assistance and initiation of an organization, in order to continuing the palm-sugar-maker community to operating and growth independently. The results obtained during the full one-month intensive mentoring period were: the better sugar products with clear & catchy branding, a wider offline marketing network through modern retail and online media, a business license for P-IRT, and a well-structured-organization for management of the Kelapa-Mas palm-sugar household industry community organization